Risk perception of healthcare workers in the first wave of the COVID-19 pandemic in Brazil - Griesi, Joana Muraguti [UNESP]; Bernardes, João Marcos [UNESP]; Alonso, Melissa [UNESP]; Gómez-Salgado, Juan; Ruiz-Frutos, Carlos; Fagundo-Rivera, Javier; López-López, Daniel; Camacho-Vega, Juan Carlos; Dias, Adriano [UNESP] (Elsevier, 2024)
Objectives: To validate the items of the Emotional Impact Questionnaire coronavirus disease-2019 (COVID-19) related to risk perception, estimating its degree, among healthcare workers in the first wave of COVID-19 pandemic, identifying possible associated factors. Methods: cross-sectional study in 1872 healthcare workers of Brazil. The population was characterized by sociodemographic and occupational information, knowledge about COVID-19, quality of information received, risk perception and preventive measures about the disease, and sense of coherence. Results: Being divorced, having a chronic disease, spending more than 1 h per day getting informed about COVID-19, and always or almost always wearing a mask regardless of symptoms, as well as self-perception of health were associated with high-risk perception. An inverse association was found between risk perception, sense of coherence and not knowing if one has had occasional contact with confirmed COVID-19 cases. Conclusion: Risk perception is influenced by emotions, experiences, and knowledge. Sense of coherence and resilience have a role in reducing risk perception. Understanding risk perception is crucial for developing effective strategies to mitigate the impact of the COVID-19 pandemic and other similar scenarios.
Keywords: COVID-19; Epidemiology; Healthcare workers; Preventive behaviours; Risk perception; Sense of coherence